Open Innovation and Implementation of Different Types of Innovation: An Analysis Based on Panel Data - Humberto Rodrigues Marques; Ednilson Sebastião Ávila; Rafael Morais Pereira; André Luiz Zambalde (BBR: Brazilian Business Review)
This work aimed to verify, based on the open innovation strategy, how different types of interactions with external actors (customers, competitors, suppliers, universities, and consultants) influence different types of innovations (general innovations, product innovations, and technological innovations) implemented by organizations. The panel data technique was used for analysis, based on PINTEC data, an innovation survey conducted by IBGE, which referred to the years 2003, 2005, 2008, 2011, and 2014. Regarding the innovations implemented by organizations, no type of interaction was significant for the general innovations or interactions with consultants, and suppliers were negative for product innovation. Finally, interaction with customers was positive while interaction with universities was negative for technological innovations. Thus, the results were essential to proving that different forms of cooperation have different impacts on the implementation of different types of innovation by organizations.